Weathering the Silver Tsunami: Dementia Community Service in Singapore - Ting, Chuong Hock; Lim, W.P. (Elsevier Masson SAS, 2016)
Introduction The prevalence of dementia rises with the rapidly increasing elderly population in developed world. In Singapore,10% of the elderly population is estimated to have dementia. Other than physical and psychological needs, social welfare should also be addressed with the support of specialised geriatric care sources to improve their quality of life.